Shale gas development in China: Implications for indoor and outdoor air quality and greenhouse gas emissions - Yanxu Zhang; Haikun Wang; Yun Han; Danhan Wang; Ge Zhu; Xi Lu (Environment International, 2020)
Holding the largest recoverable reserves over the world, China makes an ambitious plan to increase shale gas production. Here we use an integrated approach to quantify its impact on indoor and outdoor air quality and greenhouse gas emissions. This approach includes emission estimation, three-dimensional atmospheric chemistry modeling, and human health assessment. Although the production of shale gas generates PM2.5, this risk is outweighed by the benefits of the decreased PM2.5 resulted from coal combustion when shale gas replaces coal as a fuel source. The total avoided premature deaths are 14,000 (10,650–17,160 as 95% confidence interval) and 13,400 (10,350–17,100) in 2017, resulted from the outdoor and indoor pathways, respectively. Future scenario analysis suggests deploying shale gas in the residential sector, but the greenhouse gas emission reductions are minimal if replacing biomass fuel. In production regions, a net deterioration of air quality is predicted if deploying shale gas in the power and industrial sectors, but a net benefit is calculated if deploying in the residential sector. Our study calls for more stringent emission control during upstream processes, and comprehensive consideration of the cost and benefits in both the production and consumption regions.